Effects of reward and punishment in prosocial video games on attentional bias and prosocial behaviors. (December 2022) - Yin, Mengyun; Qiu, Boyu; He, Xu; Tao, Zhiyuan; Zhuang, Chengrong; Xie, Qiheng; Tian, Yu; Zhang, Wei
Abstract: Based on the General Learning Model, previous studies have examined how video game content affects players' post-game attentional bias toward prosocial information and prosocial behaviors. However, these studies ignored the reward and punishment players received for their behaviors in video games. In this study, we tested the effects of reward and punishment on players' post-game attentional bias toward prosocial information measured by the spatial cueing task and their prosocial behaviors measured by the maze selection task. In Experiment 1, reward and punishment were controlled to reconfirm the effect of prosocial content in the video game. In Experiment 2, participants were assigned to one of three conditions: being rewarded for prosocial behaviors, being punished for not performing prosocial behaviors, or not receiving feedback in the video game. The results showed that prosocial content in the video game predicted increased post-game attentional bias toward prosocial information and prosocial behaviors, and the attentional bias was amplified through punishments. In addition, the results from a reinforcement learning computational model suggested that participants learned prosocial behaviors faster in the punishment condition than in the reward condition. The results contribute to fostering players' prosocial behaviors through video games. Highlights: Short-term exposure to prosocial video games could increase post-game prosocial behaviors. Participants in the punishment condition had a greater attentional bias toward prosocial information. Participants learned prosocial behaviors faster in the punishment condition than in the reward condition. Learning rate predicted in-game prosocial behaviors and post-game attentional bias toward prosocial information.